LO08: A randomized, controlled comparison of electrical versus pharmacological cardioversion for emergency department patients with atrial flutter. (May 2020) - Stiell, I.; Sivilotti, M.; Taljaard, M.; Birnie, D.; Vadeboncoeur, A.; Hohl, C.; McRae, A.; Rowe, B.; Brison, R.; Thiruganasambandamoorthy, V.; Macle, L.; Borgundvaag, B.; et al.
Abstract : Introduction: For rhythm control of acute atrial flutter (AAFL) in the emergency department (ED), choices include initial drug therapy or initial electrical cardioversion (ECV). We compared the strategies of pharmacological cardioversion followed by ECV if necessary (Drug-Shock), and ECV alone (Shock Only). Methods: We conducted a randomized, blinded, placebo-controlled trial (1:1 allocation) comparing two rhythm control strategies at 11 academic EDs. We included stable adult patients with AAFL, where onset of symptoms was <48 hours. Patients underwent central web-based randomization stratified by site. The Drug-Shock group received an infusion of procainamide (15mg/kg over 30 minutes) followed 30 minutes later, if necessary, by ECV at 200 joules x 3 shocks. The Shock Only group received an infusion of saline followed, if necessary, by ECV x 3 shocks. The primary outcome was conversion to sinus rhythm for ≥30 minutes at any time following onset of infusion. Patients were followed for 14 days. The primary outcome was evaluated on an intention-to-treat basis. Statistical significance was assessed using chi-squared tests and multivariable logistic regression. Results: We randomized 76 patients, and none was lost to follow-up. The Drug-Shock (N = 33) and Shock Only (N = 43) groups were similar for all characteristics including mean age (66.3 vs 63.4 yrs), duration of AAFL (30.1 vs 24.5 hrs), previous AAFL (72.7% vs 69.8%), median CHADS2 score (1 vs 1), and mean initial heart rate (128.9 vs 126.0 bpm). The Drug-Shock and Shock only groups were similar for the primary outcome of conversion (100% vs 93%; absolute difference 7.0%, 95% CI -0.6;14.6; P = 0.25). The multivariable analyses confirmed the similarity of the two strategies (P = 0.19). In the Drug-Shock group 21.2% of patients converted with the infusion. There were no statistically significant differences for time to conversion (84.2 vs 97.6 minutes), total ED length of stay (9.4 vs 7.5 hours), disposition home (100% vs 95.3%), and stroke within 14 days (0 vs 0). Premature discontinuation of infusion (usually for transient hypotension) was more common in the Drug-Shock group (9.1% vs 0.0%) but there were no serious adverse events. Conclusion: Both the Drug-Shock and Shock Only strategies were highly effective and safe in allowing AAFL patients to go home in sinus rhythm. IV procainamide alone was effective in only one fifth of patients, much less than for acute AF.